Influence of Replacement of Rice Bran by Dried Brewers’ Grains on Nutrient Digestibility, Milk Production and Composition in Cows - Naik, P.K.; Swain, B.K.; Chakurkar, E.B.; Singh, N.P. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to find out the effect of replacement of rice bran by dried brewers’ grains (BG) on nutrient digestibility, milk production and milk composition in lactating cows. Based on body weight and daily milk yield, six dairy cows (avg. BW = 402.5 kg; avg. milk yield = 5.34 kg) were divided into two equal groups (GRB and GBG). They were randomly fed two iso- itrogenous concentrate mixtures i.e. with 22% rice bran or 25% dried BG along with ad lib. jowar straw and limited green fodder. The dried BG based concentrate mixture had lower ash and AIA content. There was no difference in DM intake between the groups. There was increase (P<0.05) in digestibility of DM (53.72 vs. 59.88%), CF (46.70 vs. 56.33%) and NFE (66.19 vs. 69.47%) in cows fed dried BG. The TDN content (63.96 vs. 69.07%) of the ration increased significantly (P<0.05) due to feeding of dried BG; however, the CP and DCP content was similar. The milk yield, 4% FCM yield, FCR and milk composition (fat and SNF) was similar in both the groups. The cost of the feed/d was lower (P<0.05) in group GBG (`109.61/- vs. ` 103.53/-), however, a higher net profit of ` 17.84/- per cow per day was found due to feeding of dried BG. Hence, dried brewers’ grains could be included in the concentrate mixture of dairy animals up to 25% by replacing the rice bran.